A Handful of Soil: An Ecocritical Reading of Land in Randa Abdel-Fattah’s Where the Streets Had a Name - M.M., National University of Malaysia (UKM), Raihanah; Ahmed, National University of Malaysia (UKM), Hamoud Yahya; Hashim, National University of Malaysia (UKM), Ruzy Suliza (Asiatic: IIUM Journal of English Language and Literature, 2014)
This article explores how Randa Abdel-Fattah (1979-), a Palestinian-Egyptian Australian diasporic writer, engages with the land as being ecocritically functional in her Palestinian-centred novel Where the Streets Had a Name (2008). The premise of the article is that a fictional representation of the Palestinian struggle for emancipation against occupation can be read for its environmental concerns; in particular, for the representation of the intersections of nature and culture. To this end, the article proposes a tripartite approach in reading politics of environment in the narrative by focusing on the effects of land on mind, body and voice. The analysis is carried out through the lens of ecocriticism and it reveals the symbiotic interconnections between humans and land. The findings reveal that the crisis experienced by the Palestinians in Abdel-Fattah's fiction goes beyond the need to preserve their past as the land has strong implications on their present state of mind, body and voice.